Effects of HIIT Model Progressive Sprint-Release and TUJA Shuttle Run in increasing aerobic capacity, anaerobic capacity, and speed: a comparative study in female volleyball athletes - Tutur Jatmiko; Rizky Muhammad Sidik; Nining Widyah Kusnanik; Tri Setyo Utami; Muhammad Labib Siena Ar Rasyid; Wahyu Renandi Aji (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The HIIT training model has many variations and these variations are known to have a positive effect on physical improvement.